2022
DOI: 10.1101/2022.02.14.480162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architecture and self-assembly of the jumbo bacteriophage nuclear shell

Abstract: Bacteria encode myriad defenses that target the genomes of infecting bacteriophage, including restriction-modification and CRISPR/Cas systems. In response, one family of large bacteriophage employs a nucleus-like compartment to protect their replicating genomes by excluding host defense factors. However, the principle composition and structure of this compartment remain unknown. Here, we find that the bacteriophage nuclear shell assembles primarily from one protein, termed chimallin. Combining cryo-electron to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 97 publications
5
14
0
Order By: Relevance
“…Here we characterize Goslar infecting E. coli and demonstrate that this phage also has a complex replication cycle with both a nucleus-like compartment and a tubulin-based cytoskeleton that rotates it (Figure 7). Our findings regarding the Goslar phage nucleus are supported by our recent work showing that Goslar chimallin shares high structural homology with chimallin from other jumbo phages like 20142-1, and assembles into a flexible lattice that is the primary component of the Goslar nuclear shell (Laughlin et al, 2022). Surprisingly, Goslar PhuZ filaments assemble a vortex-like cytoskeletal structure in which filaments wrap around the entire phage nucleus and project radially toward the membrane (Figure 7).…”
Section: Discussionsupporting
confidence: 84%
“…Here we characterize Goslar infecting E. coli and demonstrate that this phage also has a complex replication cycle with both a nucleus-like compartment and a tubulin-based cytoskeleton that rotates it (Figure 7). Our findings regarding the Goslar phage nucleus are supported by our recent work showing that Goslar chimallin shares high structural homology with chimallin from other jumbo phages like 20142-1, and assembles into a flexible lattice that is the primary component of the Goslar nuclear shell (Laughlin et al, 2022). Surprisingly, Goslar PhuZ filaments assemble a vortex-like cytoskeletal structure in which filaments wrap around the entire phage nucleus and project radially toward the membrane (Figure 7).…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, we previously reported that experimentally arrested infections left a stable DNA puncta at the pole, with no degradation of phage DNA by restriction enzymes 5 . This protective structure could be the “round compartments” 25 or “unidentified spherical bodies” 26 revealed by recent electron microscopy studies. The experiments reported here identified some of the likely IB protein components of this structure and uncovered a novel immune strategy that apparently destabilizes it, rendering the phage DNA susceptible to cytoplasmic nucleases.…”
Section: Discussionmentioning
confidence: 96%
“…A remarkable case of enzyme exaptation for a structural role in viruses are the major proteins of the nucleus-like shell formed by certain jumbo phages for protection of the virus DNA from cellular defense systems, such as restriction endonucleases and CRISPR-Cas (Guan and Bondy-Denomy, 2020). Structural comparisons showed that the major shell protein, chimallin, comprises two domains, the N-terminal domain with an α+β fold similar to that of an uncharacterized bacterial protein, and the C-terminal domain that is derived from a GCN5-related Nacetyltransferase most similar to E. coli AtaT and homologous to tRNA-acetylating toxins (Laughlin et al, 2022). Notably, as in many other cellular enzymes exapted by viruses, the acetyltransferase active site residues of chimallin are mutated, apparently abrogating the enzymatic activity.…”
Section: Exaptation Accompanied By Radical Functional Changementioning
confidence: 99%